Microstructuring of metal effect pigments in functional coatings on textile substrate. Issue 4 (3rd April 2017) - Mahltig, Boris; Zhang, Jieyang; Huth, Miriam-Anna; Fahmi, Amir
Abstract : A coating system for polyester fabrics is developed containing metal effect pigments and a polyurethane binder. The metal pigment is made of copper, is of microscaled size and anisotropic shape. It is originally used for optical modification but can also be used to introduce other functional properties. The polyurethane binder is needed to fix the pigments on the textile surface. The aim of the current investigation is to present that the binder has not only the task to fix the pigment but can be also used to structure the pigment surface. The binder application leads to formation of microstructures on top of the pigment surface, probably as a result of a dewetting process. Based on this microstructured pigment surface, in future, textile coatings for improvement of water-repellent, antimicrobial, and antistatic properties could be developed.